2013
DOI: 10.2337/db12-1714
|View full text |Cite
|
Sign up to set email alerts
|

High-Glucose Environment Enhanced Oxidative Stress and Increased Interleukin-8 Secretion From Keratinocytes

Abstract: Impaired wound healing frequently occurs in patients with diabetes. Interleukin (IL)-8 production by keratinocyte is responsible for recruiting neutrophils during healing. Intense inflammation is associated with diabetic wounds, while reduction of neutrophil infiltration is associated with enhanced healing. We hypothesized that increased neutrophil recruitment by keratinocytes may contribute to the delayed healing of diabetic wounds. Using cultured human keratinocytes and a diabetic rat model, the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 35 publications
7
114
1
1
Order By: Relevance
“…Egf belongs to a family of growth factors that regulate cell proliferation and migration by binding to epidermal growth factor receptor (Egfr) on the cell surface. Increased phosphorylatedepidermal growth factor receptor (p-Egfr) has been associated with the skin during diabetes in an oxidative stressprone environment (32). In a similar first compared basal levels of these genes in the normal and diabetic rat skin (unwounded).…”
Section: Resultsmentioning
confidence: 99%
“…Egf belongs to a family of growth factors that regulate cell proliferation and migration by binding to epidermal growth factor receptor (Egfr) on the cell surface. Increased phosphorylatedepidermal growth factor receptor (p-Egfr) has been associated with the skin during diabetes in an oxidative stressprone environment (32). In a similar first compared basal levels of these genes in the normal and diabetic rat skin (unwounded).…”
Section: Resultsmentioning
confidence: 99%
“…5,54,55) In the current study, the harmful effects of diabetes were also detected in our histopathological, immunohistochemical, Doppler and microangiographical assays. The semiquantitative histopathological findings of our study showed enhanced capillary density and fibroblast proliferation and decreased necrosis in peripherally CGA-treated rats compared with the PBS-treated rats.…”
Section: Fig 4 Regional Blood Perfusion In the Skin Flapsmentioning
confidence: 93%
“…16) Chronic hyperglycemia induces pathological changes in tissues, delays wound healing and increases the predisposition to infections. 5,54,55) CGA has been reported to modulate blood glucose levels and exhibits protective effects against tissue changes in diabetes. 41) CGA has been shown to exhibit hypoglycemic activity at a 27 mg/kg dosage in streptozotocin diabetic rats within 11 d 24) or 5 mg/kg/day orally for 45 d in streptozotocin-nicotinamide-induced diabetes.…”
Section: Fig 4 Regional Blood Perfusion In the Skin Flapsmentioning
confidence: 99%
“…Increased oxidative stress in diabetes is due to an imbalance between the production of ROS and the protection by cellular antioxidants (4,5,31). GSH plays important roles in antioxidant defense.…”
Section: Discussionmentioning
confidence: 99%
“…Refractory skin wound healing in diabetic patients represents a challenging medical and societal problem leading to a substantial reduction in quality of life (3). Previous studies demonstrated that sustained hyperglycemia induces excessive production of reactive oxygen species (ROS) (4). Excess ROS causes multiple cellular components damage, including excessive oxidation of lipids and proteins.…”
mentioning
confidence: 99%